2015
DOI: 10.1007/s10238-015-0390-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased inflammatory markers with altered antioxidant status persist after clinical recovery from severe sepsis: a correlation with low HDL cholesterol and albumin

Abstract: Markers of oxidative stress and antioxidant status in relation to inflammatory mediators in septic patients (SPs) during the course of sepsis and after recovery were analysed. Patients were 30 critically ill adults in severe sepsis/septic shock, 19 of which completed 3 samplings (S1: within 24 h after onset of sepsis, S7: 7 days after S1, R7: 7 days after clinical recovery). Comparing SPs with healthy controls (HCs), enhanced C-reactive protein, procalcitonin, bilirubin and CuZn-superoxide dismutase activity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 64 publications
(62 reference statements)
1
16
1
2
Order By: Relevance
“…A study by Sullivan et al found that inflammation, particularly as reflected by IL-6 and CRP levels, appears to be a powerful determinant of albumin [46]. In this connection, systemic inflammation was found not only to reduce albumin synthesis but also to increase its degradation and promote transcapillary leakage [47]. As in the present study, earlier research demonstrated that nutritional status was closely associated with the degree of frailty [48][49][50].…”
Section: Discussionsupporting
confidence: 71%
“…A study by Sullivan et al found that inflammation, particularly as reflected by IL-6 and CRP levels, appears to be a powerful determinant of albumin [46]. In this connection, systemic inflammation was found not only to reduce albumin synthesis but also to increase its degradation and promote transcapillary leakage [47]. As in the present study, earlier research demonstrated that nutritional status was closely associated with the degree of frailty [48][49][50].…”
Section: Discussionsupporting
confidence: 71%
“…Another study found, TNF-α, IL-10, and markers of oxidative stress were in negative correlation with HDL cholesterol and albumin. Resolution of the inflammation is probably the primary prerequisite to the normalization of the serum albumin [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypoalbuminemia show severe deficits in cellular immunity. The correlation between marked oxidative stress and low levels of serum albumin is supported by some clinical studies [94]. The potent antioxidant capacity of albumin administration can explain its beneficial effect.…”
Section: Hypoalbuminemia In Critically Ill Patientsmentioning
confidence: 89%